Implementasi dan Capaian SIDa di Kabupaten Blora Tahun 2012-2015 - Tri Risandewi (Research and Development Agency Ministry of Home Affairs, 2017)
Increasing competitiveness between regions is an important agenda in realizing the welfare of the community. The development of regional innovation system (SIDa) is one of the main strategies in the national innovation system that accommodates the interaction process between components of innovation system strengthening. The purposes of this study are to measure and describe the condition of policy implementation also the conditions of development achievements of institutional development networking and resources. This research chose Blora Regency as the target that has done SIDa development policy. Method that used in this research is analysis qualitative and quantitative. The type of this research is qualitative descriptive of SIDa strengthening implementation in Blora regency from 2012 until 2015. This research yields description of SIDa strengthening condition in research location covering policy scope and arrangement of SIDa elements. SIDa’s strengthening condition at the policy level in Blora Regency has only reached NPS of 6.9 and is in the middle category. If seen from the level of implementation of SIDa policy, the Government of Kabupaten Blora recently submitted the draft Regulation of Blora Regent on SIDa. Judging from the achievement of institutional arrangement, networking, and resource of SIDa of Blora Regency is 6,6 for institute, 6,5 for networking, and 5,6 resource. Based on the results of this study, the recommendations that need to be done are continiu the SIDa strengthening agenda and synchronizing innovation development with various existing programming and development agenda, conducting consistent and sustainable main and thematic development.